Examining Risk and Trust in Student Mobile Banking Adoption: An Extended Technology Acceptance Model Perspective - Rahma, Felinda Aprilia; Ulfah, Siti Zayyana (International Journal of Informatics and Information Systems, 2025)
This study examines the influence of trust, compatibility, satisfaction, perceived risk, and risk acceptance on students’ intention to use mobile banking applications. As mobile banking becomes increasingly popular for its convenience and efficiency, especially among tech-savvy youth, understanding the behavioral factors influencing adoption is crucial. Utilizing an extended Technology Acceptance Model (TAM), this study employs a quantitative approach with multiple linear regression analysis. The dataset, comprising responses from 219 Indonesian university students, was drawn from the